UNDERSTANDING THE CONTEXTUAL FACTORS THAT INFLUENCE VILLAGE HEALTH SANITATION AND NUTRITION COMMITTEES IN NORTHERN INDIA. (7th July 2016) - Scott, Kerry; Sheikh, Kabir; George, Asha; Garimella, Surekha; Mondal, Shinjini; Patel, Gupteswar; Ved, Rajani
Abstract : Background: Health committees are a popular strategy for facilitating community participation in health, particularly in low- and middle-income countries. Their potential effects are mediated by a number of factors including the contextual environment in which they function. George and colleagues1 in 2015 put forward a framework that identifies four contextual spheres – porous and interconnect – that are most relevant to health committees: community, health facility, health administration and society. We apply this framework to an in-depth contextual analysis of an intervention to strengthen Village Health Sanitation and Nutrition Committees (VHSNCs) in rural north India, examining features in each sphere that influenced VHSNC outcomes. Methods: Over the course of 18 months, 50 marginalised villages in a north Indian state received a government-designed and NGO-facilitated VHSNC support package, which included social mobilisation, VHSNC membership expansion, training and on-going facilitation for committee meetings and activities. Qualitative research through interviews (n=74), focus groups (n=18) and observation explored the contextual features that facilitated or hindered intensified community engagement by VHSNCs. Thematic network analysis enabled the identification and grouping of themes, and detailed exploration of sub-themes. Findings: VHSNCs attempted to improve access to drinking water, expand immunisation coverage, secure nurses, doctors, and medical supplies for health centres, and improve the functioning of village schools and Anganwadi centres. Most action took the form of writing appeals to various government officials. Some VHSNCs contributed to concrete improvements, namely having a doctor re-posted to a health centre and enabling school children to access government benefits (free bicycles and a scholarship for orphans), and many people appreciated learning about health topics and health rights. However, success was modest within the period under study (12 months) and although VHSNC members appreciated some aspects of the intervention, there was also significant disappointment. Within the community sphere, VHSNCs were challenged by social hierarchies that prevented people from speaking out about local issues. Women's active participation was particularly curtailed by community concerns that village-level monitoring would disturb social harmony and gender norms. In addition, communities exhibited deep mistrust of government institutions, which made people wary of investing in VHSNC. Within the health facility sphere, VHSNCs were hindered by the severely under-resourced health system. VHSNCs faced a need for increased support to enable frontline health workers to facilitate their functionality. Within the health administration sphere, block-level health functionaries often lacked the power to respond to VHSNC requests – particularly so for hiring additional nurses and doctors to fill vacancies – leaving VHSNCs unsure of how to bring about much needed change. The chain of responsibility for aspects of VHSNC administration was opaque, which, for example, made it difficult for VHSNCs to identify why their INR 10, 000 (USD 150) yearly untied fund was not released throughout the 18 months period. Furthermore, despite VHSNCs' inter-sectorial nature – working on health, sanitation and nutrition – they struggled to involve diverse government services and were only officially mandated by the Ministry of Health and Family Welfare. In the societal sphere, despite decentralisation reforms that empowered the locally elected system of government ( Panchayat ), many VHSNCs were still unable to engage the powerful elected representative ( Sarpanch ), and instead worked with the lowest-level elected representative ( Ward Panch ), who they considered powerless. Media engagement emerged as a potential avenue to effect change. The prevalence of market solutions to fill gaps in government service provision (such as private health care, schools and wells) reduced the willingness of some people to work on VHSNC activities, since they were already paying for private services. Discussion & recommendations: Active facilitation by a dedicated NGO enabled VHSNCs to work with or overcome many community-level challenges to become functioning local bodies that took action to improve local health. The VHSNC-support intervention succeeded in its core elements of expanding committee membership through a participatory process, training VHSNC members, facilitating monthly meetings and helping VHSNCs to take local actions for health. Yet major contextual barriers at the community, health facility, administration and societal levels limited VHSNCs' capacity to improve local health services. We identify features of a supportive environment for VHSNCs. At the community level, VHSNCs would be bolstered by greater legitimacy through early successes, an emphasis on collaborative and supportive local monitoring, and focused capacity building for female engagement. At the health facility level, VHSNCs need minimally functional health services which to engage. Filling healthcare staff vacancies must therefore be a priority. On-going support and incentives for frontline health functionaries to facilitate VHSNCs would institutionalize the VHSNCs' functionality. VHSNCs would be more effective if they were able to understand clear pathways of accountability for services, so that VHSNC members know where to go to seek change. Making VHSNC support and funding a top-down responsibility rather than a bottom-up battle is vital for VHSNC sustainability. Finally, inter-sectorial coordination of health, sanitation and nutrition at higher levels of government would generate a more VHSNC-enabling context. At the societal level, VHSNCs would benefit from additional decentralisation of power, so that ward members can take village-level action, from the development of media engagement strategies, and at the broadest level, from robust public funding for universal health, nutrition and sanitation services so that no one has to rely on the private sector to secure the basic requirements for health and wellbeing. Grant funding (WHO's Alliance for Health Policy and Systems Research, Government of Canada's International Development Research Centre, National Health Systems Resource Centre) for research but no other competing interests